Individuals’ Psychological Responses to the Economic Crisis and the Media: Lessons Learned From New York - Matsaganis, Matthew D; Jo, Hyerim; Seo, Mihye (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2018)
In this paper we synthesize findings from two studies conducted in the context of a larger research project launched in the metropolitan area of New York City – the epicenter, in the U.S., of what evolved into a global economic crisis in 2008. The larger project’s overarching goal has been to investigate social factors, individual and contextual, that shaped residents’ responses to the crisis. In the first study we draw on data collected through an online survey in 2011 (N = 387), and data from the U.S. Census Bureau and the U.S. Department of Labor; in the second study we rely on survey data collected from New York City residents in 2012 (N = 338).